The Equity Theory Study in Increasing Job Satisfaction at the Banyumas Regency Environmental Service - Fatwa Zuhaena; Ratna Pujiastuti; Herwiek Dyah Lestari (Bulletin of Community Engagement, 2025)
The study demonstrates that organizational justice is a significant factor in enhancing employee job satisfaction within the public sector organizations. The findings reveal that employees are more likely to experience positive work attitudes when they perceive fairness in organizational outcomes, decision-making procedures, interpersonal treatment, and information sharing. These results confirm that organizational justice should be viewed as a multidimensional construct that collectively shapes employees’ workplace experiences and satisfaction. The study strengthens the relevance of Equity Theory, Need Fulfillment Theory, and organizational justice literature by showing that fairness perceptions remain essential in contemporary public sector organizations organizations characterized by high performance expectations and regulatory demands. The findings also highlight that employee satisfaction is influenced not only by tangible rewards but also by the quality of organizational processes and interactions. From a practical perspective, public sector organizations should prioritize the development of fair compensation systems, transparent procedures, respectful supervisory practices, and effective communication mechanisms. Such initiatives can contribute to a more positive work environment and improve employee satisfaction. This study is limited by its cross-sectional design and geographical focus on selected public sector organizations in Central Java. Future research is encouraged to employ longitudinal approaches, include broader organizational settings, and examine additional variables such as organizational trust, employee engagement, or psychological safety to provide a deeper understanding of the relationship between organizational justice and employee outcomes